DM Reviews – June 2018. Issue 1 (27th July 2018) - Litta, Eleonora; Manos, Traianos; Davis, Lisa Fagin
Abstract : These are three reviews for Digital Medievalist, published in order of acceptance. In the first review, Eleonora Litta reviews Bodard, Gabriel and Matteo Romanello's (2016) Digital Classics outside the Echo-Chamber: Teaching, Knowledge Exchange and Public Engagement. Digital Classics Outside the Echo-Chamber is mainly addressed to Digital Humanists. It showcases exciting methodological examples of the application of digital tools to the Humanities, and demonstrates their impact on pedagogy and public outreach. In the second review, Traianos Manos reviews the online database ALIM: Archivio della Latinità Italiana del Medioevo. The Archive of the Italian Latinity of the Middle Ages (http://en.alim.unisi.it/ ), which aims "to provide free online access to all the Latin texts produced in Italy during the Middle Ages". After presenting Archive's new website, the review discusses issues in editorial approach, usability, digital tools available and more. It concludes that the Archive, wherein there are still opportunities for further enhancements, is one of the most important digital libraries of medieval Latin texts that exist today. For the final review, Lisa Fagin Davis reviews Codicology and Palaeography in the Digital Age 4. Codicology and Paleography in the Digital Age 4 (henceforth CPDA4) continues the series of volumes that began with the proceedings of a 2009 conference, in this case combining solicited contributions to the proceedings of the "Machines and Manuscripts" conference organized under the auspices of the eCodicology project and held in Trier, Karlsruhe and Darmstadt, 2014–2016. Contributions are by senior and junior digital scholars, working alone or in teams, presenting works both in-progress and complete. CPDA4 thus functions as a "state of the field, " focusing more on case studies and methodology than theory, demonstrating how the theoretical approaches of the previous volumes can be put into action. The editors have chosen to divide the volume into two sections, "Digital Codicology" and "Digital Paleography." Contributions are in English or German, with abstracts in both languages. Each contribution is accompanied by a detailed bibliography listing both printed and online resources.